Atomistic deformation mechanisms of amorphous/polycrystalline metallic nanolaminates. (April 2018) - Zhao, L.; Chan, K.C.; Chen, S.H.
Abstract: A series of multilayer amorphous Cu50 Zr50 /Cu nanolaminates with consideration of grain boundary characteristics in the Cu layers were constructed and compressed to investigate the atomistic mechanisms of yielding and plastic deformation behavior using large-scale atomistic simulations. The results revealed that yielding occurs initially in the Cu layers through lattice dislocations, while plastic deformation in the amorphous layers is induced by the transfer of dislocation plasticity from the Cu layers, mainly at the intersections of the crystalline-amorphous interfaces and grain boundaries. Similar to the roles of defects-like secondary phases, the Cu layers serve as sites for heterogeneous nucleation of embryonic shear bands, as well as barriers to their propagation into mature ones. The coupled interplay between the crystal plasticity and the glassy plasticity in the nanolaminates promotes a more homogeneous redistribution of plastic deformation, providing a kind of hardening mechanism. In addition, our simulations also demonstrate a transition of the deformation mode from localized to homogeneous-like deformation by tailoring the relative volume fraction of the Cu layers. The findings provide more detailed atomistic information for understanding the underlying deformation mechanisms that are difficult to obtain by post-mortem observations and are useful for optimizing the structure of amorphous/crystalline metallic nanolaminates. Highlights: The deformation mechanisms of Cu50 Zr50 /polycrystalline Cu nanolaminates were investigated. Yielding occurs initially in the Cu layers through dislocations, which further trigger plasticity in the amorphous layers. Cu phases serve as heterogeneous sites for nucleating shear bands as well as barriers to their propagation. Interplay between crystal plasticity and glassy plasticity promotes homogeneous plastic deformation.